Relación entre el conocimiento de la problemática ambiental y la formación del pensamiento ecológico positivo de los alumnos del 5to grado de secundaria de las I.E del distrito de Rioja - Garcia Jimenez, Enrrique (2012)
Already more than a decade ago has been inserted into the scope of the educational process the concept of learning achievement, the same meaning that projects towards a holistic understanding of the formation of the learner. The inexorable advance of environmental degradation prompted our curiosity to scrutinize what is the status of this process in schools and levels of achievement in the field of internalisation of concepts and thoughts on this important axis line currículum. The research aimed to study in the fifth grade of secondary level educational institutions in the Rioja district to verify the link between these two variables as learning skills in students. These two qualitative variables: knowledge of environmental issues and ecological thinking positive and two links of the macro skills necessary to train students environmentalist eco. Based on a theoretical framework that describes the environmental problem as a parameter to incorporate cognitive science learning as well as the accuracy of a small study of thought and purpose as an active component such as a verifiable incorporating evaluative attitudes and training behavioral learning a favorable position. Our objective was to describe the possible association between knowledge of environmental issues and the formation of positive ecological thinking of fifth grade students of secondary level educational institutions in the district of Rioja taking 30 students as part of the population. The investigation was set to a descriptive correlational design, with the media and a scale test for verification of data, which was applied only once. Data processing focused on the extraction of the average frequencies observed in all the indicators evaluated, using the calculation of Pearson's correlation coefficient to take the test of the hypothesis thus failed to demonstrate that there is a probable significant level association between the variables studied.